Direct plant regeneration from hypocotyl and cotyledon explants of five different sunflower genotypes (Helianthus annus L.) from Turkey - (:unkn) unknown (DIAGNOSIS PRESS LTD, 2002)
This study aims to establish plant tissue culture and regeneration systems of five different sunflower (Helianthus annuus L.) genotypes: Trakya 259, Trakya 80, Trakya 129, Trakya 2098 and Viniimk 8931, which are commercially important for Turkey. Plant tissue culture systems were established on Murashige and Skoog (MS) media supplemented with various plant growth regulators using hypocotyl and cotyledon explants. The highest shoot regeneration was observed using hypocotyl explants with Trakya 259 genotype (40 %) on MS media supplemented with 1 mg/l BAP (6-benzylaminopurine) and 0.5 mg/l NAA (a-naphthalene acetic acid). Hypocotyl explants from other genotypes showed regeneration efficiencies as followed: Trakya 80, 33 %; Trakya 129, 29 %; Trakyu 2098, 22 % and Viniimk 8931, 19 %. Shoot regeneration efficiencies with the cotyledon explants on the same medium were lower in comparation with hypocotyl explants as followed: Trakya 129, 20 %; Trakya 2098, 10 % and Viniimk 8931, 9 %. In addition, two genotypes (Trakya 259 and Trakya 80) were non-responsive on the same media with cotyledon explants. All of the regenerated shoots were rooted on MS media supplemented with 1 mg/l IBA (indol-3-butiric acid). The results obtained in this study will be useful for the improvement of gene transfer systems to these commercially important sunflower genotypes.
Keywords: SOMATIC EMBRYOGENESIS; HIGH-FREQUENCY; CULTURE; CALLUS